2011
DOI: 10.1186/1471-244x-11-22
|View full text |Cite
|
Sign up to set email alerts
|

The association between bullying and early stages of suicidal ideation in late adolescents in Greece

Abstract: BackgroundBullying in schools has been associated with suicidal ideation but the confounding effect of psychiatric morbidity has not always been taken into account. Our main aim was to test the association between bullying behavior and early stages of suicidal ideation in a sample of Greek adolescents and to examine whether this is independent of the presence of psychiatric morbidity, including sub-threshold symptoms.Methods5614 pupils 16-18 years old and attending 25 senior high schools were screened in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 47 publications
2
27
0
15
Order By: Relevance
“…Moreover, these psychosocial problems may contribute to additional negative outcomes for victimized students including poor school performance, often because of frequent absences or impaired concentration (Card & Hodges, 2008;Nishina et al, 2005). In the worst cases researchers have found increased rates of suicidal ideation among victimized youth (Rigby & Slee, 1991;Skapinakis et al, 2011).…”
mentioning
confidence: 97%
“…Moreover, these psychosocial problems may contribute to additional negative outcomes for victimized students including poor school performance, often because of frequent absences or impaired concentration (Card & Hodges, 2008;Nishina et al, 2005). In the worst cases researchers have found increased rates of suicidal ideation among victimized youth (Rigby & Slee, 1991;Skapinakis et al, 2011).…”
mentioning
confidence: 97%
“…A little less than one-third of students who were psychologically abused (25.8%) and about one-third of students (29.1%) who were physically abused manifest mild anxiety symptoms. (25). The most essential step in violence prevention is directed toward the general population.…”
Section: Resultsmentioning
confidence: 99%
“…Skapinakis et al (2011) found that victims were significantly more likely to report suicidal ideations than were bullies. These negative psychological effects have been found to persist into adulthood (Graham-Bermann et al 1994).…”
Section: Effects Of Bullyingmentioning
confidence: 98%